72.4k views
3 votes
. Evaluate tan(α + β) = sin(????+????) / cos(????+????) to show tan(???? + ????) = tan(????)+tan(????????) / 1−tan(????) tan(????

. Use the resulting formula to show that
tan(2????) = 2 tan(????) / 1−tan2(????)

User Spong
by
6.2k points

1 Answer

4 votes

Answer with Step-by-step explanation:

We are given that


tan(\alpha+\beta)


(sin(\alpha+\beta)/(cos(\alpha+\beta))

By using formula
tan x=(sin x)/(cos x)


(sin\alpha cos\beta+sin\beta cos\alpha)/(cos\alpha cos\beta-sin\alpha sin\beta)

By using property:
sin(x+y)=sin x cosy+cos x sin y


cos(x+y)=cos x cosy-sin x siny

Divide numerator and denominator by
cos\alpha cos\beta

Then, we get


((sin\alpha)/(cos\alpha)+(sin\beta)/(cos\beta))/(1-(sin\alpha sin\beta)/(cos\alpha cos\beta))


tan(\alpha+\beta)=(tan\alpha+tan\beta)/(1-tan\alpha tan\beta)

Hence, proved

Substitute
\alpha=\beta

Then we get


tan 2\alpha=(tan\alpha+tan\alpha)/(1-tan^2\alpha)


tan(2\alpha)=(2tan\alpha)/(1-tan^2\alpha)

Hence, proved.

User Magali
by
5.9k points